2018
DOI: 10.1136/bmj.k1612
|View full text |Cite
|
Sign up to set email alerts
|

Association between use of systematic reviews and national policy recommendations on screening newborn babies for rare diseases: systematic review and meta-analysis

Abstract: ObjectiveTo understand whether international differences in recommendations of whether to screen for rare diseases using the newborn blood spot test might in part be explained by use of systematic review methods.DesignSystematic review and meta-analysis.Data sourcesWebsite searches of 26 national screening organisations.Eligibility criteria for study selectionJournal articles, papers, legal documents, presentations, conference abstracts, or reports relating to a national recommendation on whether to screen for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 32 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…Meta-epidemiology is a method of analysis that adopts the meta-analysis approach to examine the impact of certain characteristics of primary studies on the synthesized measure and provides empirical evidence for hypothesized associations (Bae, 2014). This method tries to investigate the effect of the characteristics of primary studies on the estimated effect of interventions rather than the effect of the intervention itself (Bae, 2014;Murad, 2017;Sian, 2018). For example, it has been shown that independent of the estimated effect of a specific intervention in clinical trials, unblinded trials usually exaggerate the estimated effect of the targeted intervention, compared to blinded trials (Hróbjartsson, 2014).…”
Section: The Problem Condition or Issuementioning
confidence: 99%
See 2 more Smart Citations
“…Meta-epidemiology is a method of analysis that adopts the meta-analysis approach to examine the impact of certain characteristics of primary studies on the synthesized measure and provides empirical evidence for hypothesized associations (Bae, 2014). This method tries to investigate the effect of the characteristics of primary studies on the estimated effect of interventions rather than the effect of the intervention itself (Bae, 2014;Murad, 2017;Sian, 2018). For example, it has been shown that independent of the estimated effect of a specific intervention in clinical trials, unblinded trials usually exaggerate the estimated effect of the targeted intervention, compared to blinded trials (Hróbjartsson, 2014).…”
Section: The Problem Condition or Issuementioning
confidence: 99%
“…Cochrane Collaboration's recommends to present meta-analyses stratified according to risk of bias or using meta-regression to compare results from studies at high and low risk of bias to clarify the effect of risk of bias in the observed results. In the present review, a sort of analysis methods (Bae, 2014;Sian, 2018) would be applied for decomposition of the heterogeneity in KT interventional studies aimed to improve use of evidence in health policymaking.…”
Section: How the Intervention Might Workmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing number of novel genetic diseases have been added to the list of pediatric liver disease etiologies. However, pediatric liver disease continues to be a major challenge around the world ( 6 ). Certain liver diseases that manifest during childhood serve as antecedents to chronic liver disease, cirrhosis, and hepatocellular carcinoma in adulthood ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, NBS cannot ignore the statement “All screening programmes do harm; some do good as well” [ 13 ]. For example, false positive screening results strain the health system and can trigger short- or long-term psychosocial distress for families (anxiety or vulnerable child syndrome), and NBS may cause overtreatment for mild forms of diseases [ 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. The ongoing expansion of NBS programmes, which is likely to continue as the use of genetic technologies widens, allows more children to benefit from NBS, but also increases the complexity of NBS structures and the number of potential harms, such as false or unclear findings.…”
Section: Introductionmentioning
confidence: 99%